Denervation‐induced muscle atrophy suppression in renalase‐deficient mice via increased protein synthesis. Issue 15 (1st August 2020) - Tokinoya, Katsuyuki; Shirai, Takanaga; Ota, Yuya; Takemasa, Tohru; Takekoshi, Kazuhiro
Abstract: Denervation‐induced muscle atrophy increases signaling through both protein degradation and synthesis pathways. Renalase is a flavin adenine dinucleotide‐dependent amine oxidase that inhibits apoptosis and inflammation and promotes cell survival. This study aimed to elucidate the effect of renalase on denervation‐induced muscle atrophy. We used 7‐week‐old renalase knock‐out (KO) mice (a model of denervation‐induced muscle atrophy) and wild‐type (WT) mice (KO: n  = 6, weight = 20–26 g; WT: n  = 5, weight = 19–23 g). After their left legs were denervated, these mice were killed 1 week later. KO mice had lighter muscle weight than the WT mice. We observed an increase in molecular signaling through protein degradation pathway as well as oxidative stress in denervated muscles compared with that in sham‐operated muscles in both WT and KO mice. Additionally, we also observed the main effect of renalase in WT and KO mice. Mitochondrial oxidative phosphorylation protein content was lower in denervated muscles than in sham‐operated muscles in both WT and KO mice. However, a significant difference was noted in the reaction with Akt and p70S6K (components of the protein synthesis pathway) between WT and KO mice. In conclusion, mice with renalase deficiency demonstrated an attenuation of denervation‐induced muscle atrophy. This might be related to catecholamines because signaling through the protein synthesis pathway was increased following denervation in renalase KO mice compared with that in WT mice, despite showing no change in signaling through protein degradation pathways. Abstract : We show that signaling through the protein synthesis pathway in the denervated limb of renalase knock‐out mice was increased compared with wild‐type mice, despite no change in signaling through protein degradation pathways.